The roles, works, and skills of paraprofessionals in academic libraries of South Manila Educational Consortium (SMEC), Mendiola Consortium, and European Studies Consortium in the Philippines - Cauilan, Bob P. (2015)
The study determined the roles, skills and tasks/works of the paraprofessional staff of the member libraries of the South Manila Educational Consortium (SMEC), Mendiola European Studies Consortium and Mendiola Consortium. It compared the existing roles, works, and skills of the paraprofessionals against those specified in the PAARL standards and RA 9246. The population included all paraprofessional staff currently employed in the member academic libraries of the three consortia through total enumerations with two hundred five (205) paraprofessionals of the member libraries of the three consortia as respondents of the study.